Fructose-containing caloric sweeteners as a cause of obesity and metabolic disorders - Tappy, Luc (Journal of experimental biology, 2018)
Compared with other carbohydrates, fructose-containing caloric sweeteners (sucrose, high-fructose corn syrup, pure fructose and fructose-glucose mixtures) are characterized by: a sweet taste generally associated with a positive hedonic tone; specific intestinal fructose transporters, i.e. GLUT5; a two-step fructose metabolism, consisting of the conversion of fructose carbones into ubiquitous energy substrates in splanchnic organs where fructolytic enzymes are expressed, and secondary delivery of these substrates to extrasplanchnic tissues. Fructose is a dispensable nutrient, yet its energy can be stored very efficiently owing to a rapid induction of intestinal fructose transporters and of splanchnic fructolytic and lipogenic enzymes by dietary fructose-containing caloric sweeteners. In addition, compared with fat or other dietary carbohydrates, fructose may be favored as an energy store because it uses different intestinal absorption mechanisms and different inter-organ trafficking pathways. These specific features make fructose an advantageous energy substrate in wild animals, mainly when consumed before periods of scarcity or high energy turnover such as migrations. These properties of fructose storage are also advantageous to humans who are involved in strenuous sport activities. In subjects with low physical activity, however, these same features of fructose metabolism may have the harmful effect of favoring energy overconsumption. Furthermore, a continuous exposure to high fructose intake associated with a low energy turnover leads to a chronic overproduction of intrahepatic trioses-phosphate production, which is secondarily responsible for the development of hepatic insulin resistance, intrahepatic fat accumulation, and increased blood triglyceride concentrations. In the long term, these effects may contribute to the development of metabolic and cardiovascular diseases.